α-Amidobenzylboronates and β-Ketobenzylboronates as Inhibitors of Plasma Kallikrein - Allison, Matthew (2024)
Hereditary angioedema (HAE), a rare genetic disorder, is associated with uncontrolled plasma kallikrein (PKa) enzyme activity leading to often severe bradykinin-induced swelling in subcutaneous and submucosal membranes in various locations of the body.